1993
DOI: 10.1063/1.465335
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a second molecular channel in the fragmentation of formaldehyde

Abstract: This paper reports CO(v,J) distributions from photolysis on the 2141, 45, 2161, 2143, and 2341 bands of H2CO and the 2243 band of D2CO. A significant fraction of the CO(v=0) photofragment is found in low rotational states (JCO<15) for excitation above the threshold of the H+HCO dissociation channel. Photolysis on the 2141 band, which lies below this radical threshold, shows no measurable population in low-JCO states. The fraction of the total population in low-JCO states increases with increasing photol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 34 publications
10
143
1
Order By: Relevance
“…The CO rotational distributions reported here for Mechanism B are quite similar to the CO rotational distributions observed in the photodissociation of formaldehyde (2). In that study, when the photolysis energy was below the threshold for the radical H ϩ HCO channel, the CO distribution was also Gaussian, and peaked at high J.…”
Section: Discussionsupporting
confidence: 66%
“…The CO rotational distributions reported here for Mechanism B are quite similar to the CO rotational distributions observed in the photodissociation of formaldehyde (2). In that study, when the photolysis energy was below the threshold for the radical H ϩ HCO channel, the CO distribution was also Gaussian, and peaked at high J.…”
Section: Discussionsupporting
confidence: 66%
“…striking signature of the second pathway, the lack of significant alignment of the CO molecular rotation relative to the velocity vector of the separating CH 4 and CO products. This implies that the abstraction of the H atom in HCO by the CH 3 fragment occurs at a variety of relative orientations.…”
Section: Attempts To Develop Fully Quantum Versionsmentioning
confidence: 99%
“…' Houston and Kable (1) report another likely example of the ''roaming'' pathway in the photodissociation of CH 3 CHO. In this case, it is the methyl radical that may be roaming about the HCO fragment and abstracting the H atom to form vibrationally excited CH 4 (and rotationally cold CO). By contrast, the CH 4 molecular product formed by the TS is not vibrationally very excited, but the CO product is rotationally excited.…”
mentioning
confidence: 99%
“…When excited by photons of sufficient energy, the formaldehyde molecule can dissociate via two channels: H2CO → H + HCO (radical channel) or H2CO → H2 + CO (molecular channel). In earlier work, van Zee et al (3) found that, above the energy threshold for the H + HCO dissociation channel, the CO rotational state distribu-tion exhibited an intriguing shoulder at lower rotational levels correlated with a hot vibrational distribution of H2 coproduct. This observed product state distribution did not fit well with the traditional picture of the dissociation of formaldehyde via the well-characterized saddle point transition state for the molecular channel.…”
Section: Formaldehydementioning
confidence: 99%